Influence of Mine Tunnel Wall Humidity on Electromagnetic Waves Propagation - Lingfei Cheng; Lili Zhang; Jie Li (International Journal of Antennas and Propagation)
High moisture in mine tunnel can cause the change of the permittivity and conductivity of tunnel walls, therefore influence the characteristics of electromagnetic waves propagation. This paper analyzes the mechanism of humidity influencing the permittivity and conductivity and attenuation of electromagnetic waves propagation in the circular tunnel and rectangular tunnel. The study result shows that, in the interest frequency range, the change of permittivity caused by humidity has little effect on propagation attenuation, but the effect on the conductivity change cannot be ignored. When the humidity is greater than a certain value, the attenuation will be increased significantly.